A New Theological Anthropology for Developing Resiliency and Healing from Combat*. Issue 1 (2nd January 2019) - Hansen, Christopher
ABSTRACT: Moral injury is a complex wound of the soul affecting many veterans returning from combat. This article will propose that a blended theological anthropology, which incorporates Irenaeus's understanding of spiritual growth and Augustine's focus on individual accountability and sin, will better foster healing and growth from morally traumatic experiences. In order to do so, I will introduce elements of the psychological paradigm of posttraumatic growth with a theological anthropology I develop in order to propose a mindset which I believe will increase resiliency to the morally challenging environment of combat.